Bites by the king cobra (Ophiophagus hannah) in Myanmar: successful treatment of severe neurotoxic envenoming. - Tin-Myint; Rai-Mra; Maung-Chit; Tun-Pe; Warrell, D (1991)
Three patients bitten by the world's largest species of venomous snake, the king cobra (Ophiophagus hannah), were observed in Myanmar (Burma). All three were involved in the famous snake dance in Yangon (Rangoon) Zoological Gardens. One patient showed no signs of envenoming despite a sustained bite, another developed only signs of local envenoming, but in a third there was severe neurotoxic envenoming requiring mechanical ventilation for 64 1/2 hours, episodes of hypotension and massive swelling of the bitten limb. This patient showed some signs of recovery before delayed treatment with specific antivenom. It is possible that all three patients had some immunity to king cobra venom resulting from traditional 'immunization' achieved by scratching venom into the skin. The literature on king cobra bites is reviewed and recommendations given for antivenom and ancillary treatments.